Reconstruction of ancestral plant genomes for inter-crop translational research - Cléa Siguret; Margaux Olivier; Cécile Huneau; Mamadou Dia Sow; Pierre-Louis Stenger; Christophe Klopp; Marie-Laure Martin; Jean-Philippe Tamby; Serguei Gorbounov; Raphael Flores; Fabrice Legeai; Matéo Boudet; et al. (Molecular Plant, 2026)

On the origin of the late-flowering ppd-H1 allele in barley - Rajiv Sharma; Salar Shaaf; Kerstin Neumann; Peter Civan; Yu Guo; Martin Mascher; Michal David; Adnan Al-Yassin; Hakan Özkan; Tom Blake; Sariel Hübner; Nora P. Castañeda-Álvarez; et al. (Theoretical and Applied Genetics, 2025)
To breed for climate resilient crops, an understanding of the genetic and environmental factors influencing adaptation is critical. Barley provides a model species to study adaptation to climate change. Here we present a detailed analysis of genetic variation at a major photoperiod response locus and relate this to the domestication history and dispersal of barley. The PPD-H1 locus (a PSEUDO-RESPONSE REGULATOR 7 ) promotes flowering under long-day conditions, and a natural mutation at this locus resulted in a recessive, late-flowering ppd-H1 allele. This mutation proved beneficial in high-latitude environments such as Northern Europe, where it allows extended vegetative growth during long spring days. We infer the origin of the mutated late-flowering ppd-H1 allele by re-sequencing a large geo-referenced collection of 942 Hordeum spontaneum , 5 Hordeum agriocrithon and 1110 domesticated ( Hordeum vulgare ) barleys. We demonstrate that the late-flowering phenotype originated from Desert-type wild barley in the Southern Levant and present evidence suggesting a post-domestication origin of the mutated ppd-H1 allele.

AP1S1 missense mutations cause a congenital enteropathy via an epithelial barrier defect - Katharina M. C. Klee; Andreas R. Janecke; Hasret A. Civan; Štefan Rosipal; Peter Heinz-Erian; Lukas A. Huber; Thomas Müller; Georg F. Vogel (Human Genetics, 2020)
Congenital diarrheal disorders (CDD) comprise > 50 monogenic entities featuring chronic diarrhea of early-onset, including defects in nutrient and electrolyte absorption, enterocyte polarization, enteroendocrine cell differentiation, and epithelial integrity. Diarrhea is also a predominant symptom in many immunodeficiencies, congenital disorders of glycosylation, and in some defects of the vesicular sorting and transporting machinery. We set out to identify the etiology of an intractable diarrhea in 2 consanguineous families by whole-exome sequencing, and identified two novel AP1S1 mutations, c.269T>C (p.Leu90Pro) and c.346G>A (p.Glu116Lys). AP1S1 encodes the small subunit of the adaptor protein 1 complex (AP-1), which plays roles in clathrin coat-assembly and trafficking between trans-Golgi network, endosomes and the plasma membrane. An AP1S1 knock-out (KO) of a CaCo2 intestinal cell line was generated to characterize intestinal AP1S1 deficiency as well as identified mutations by stable expression in KO background. Morphology and prototype transporter protein distribution were comparable between parental and KO cells. We observed altered localization of tight-junction proteins ZO-1 and claudin 3, decreased transepithelial electrical resistance and an increased dextran permeability of the CaCo2-AP1S1-KO monolayer. In addition, lumen formation in 3D cultures of these cells was abnormal. Re-expression of wild-type AP1S1 in CaCo2-AP1S1-KO cells reverted these abnormalities, while expression of AP1S1 containing either missense mutation did not. Our data indicate that loss of AP1S1 function causes an intestinal epithelial barrier defect, and that AP1S1 mutations can cause a non-syndromic form of congenital diarrhea, whereas 2 reported truncating AP1S1 mutations caused MEDNIK syndrome, characterized by mental retardation, enteropathy, deafness, neuropathy, ichthyosis, and keratodermia.

Remediating Over-Produced and Contaminated Aquifers by Artificial Recharge from Surface Waters - Peter Szucs; Tamas Madarasz; Faruk Civan (Environmental Modeling & Assessment, 2009)

Applicability of the most frequent value method in groundwater modeling - Peter Szucs; Faruk Civan; Margit Virag (Hydrogeology Journal, 2006)

Practical Method for Analysis of Immiscible Displacement in Laboratory Core Tests - Janos Toth; Tibor Bodi; Peter Szucs; Faruk Civan (Transport in Porous Media, 1998)